Preoperative preparation of woman for urogynaecological surgery - Postawski, Krzysztof; Rechberger, Tomasz; Gałecka-Josse, Magdalena; Tomaszewski, Jacek (Menopause Review/Przegląd Menopauzalny, 2008)
This paper briefly outlines the milestones in preoperative preparation of women for urogynaecological surgery. The most important is preoperative management, which includes patient evaluation, stratification of risk, and risk factor modification. The goal of the preoperative physical examination is to identify physical findings consistent with medical disease states. We also discuss in detail main preoperative indications for laboratory tests and deep vein thrombosis prophylaxis.